2020
DOI: 10.1038/s41422-020-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

A virus-induced conformational switch of STAT1-STAT2 dimers boosts antiviral defenses

Abstract: Type I interferons (IFN-I) protect us from viral infections. Signal transducer and activator of transcription 2 (STAT2) is a key component of interferon-stimulated gene factor 3 (ISGF3), which drives gene expression in response to IFN-I. Using electron microscopy, we found that, in naive cells, U-STAT2, lacking the activating tyrosine phosphorylation, forms a heterodimer with U-STAT1 in an inactive, anti-parallel conformation. A novel phosphorylation of STAT2 on T404 promotes IFN-I signaling by disrupting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Nuclear extracts from BMDMs were prepared by high salt extraction ( 36 ). Electrophoretic Mobility Shift Assays (EMSA) were conducted by using EMSA/Gel shift kit (Beyotime) with the standard method as described previously ( 38 ). The NFκB consensus oligo sequence is 5′-AGT TGA GGG GAC TTT CCC AGG C-3′ and 5′- CGG ACC CTT TCA GGG GAG TTG A -3′.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear extracts from BMDMs were prepared by high salt extraction ( 36 ). Electrophoretic Mobility Shift Assays (EMSA) were conducted by using EMSA/Gel shift kit (Beyotime) with the standard method as described previously ( 38 ). The NFκB consensus oligo sequence is 5′-AGT TGA GGG GAC TTT CCC AGG C-3′ and 5′- CGG ACC CTT TCA GGG GAG TTG A -3′.…”
Section: Methodsmentioning
confidence: 99%
“…TRAF6 could promote proinflammatory cytokines expression by activating downstream pathways of TAK1 and NFκB as aforementioned. TF STAT2, phosphorylated by TBK1, can promote innate immune response by activating its target gene IFNA1 [ 64 ]. However, ORF7a of SARS-CoV-2 has been found to interact with STAT2 as well.…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis studies have identified that phosphorylation of additional residues (S287 [24], T387 [25], S734 [26]) on STAT2 negatively regulates its transcriptional activity. STAT2 T387 is constitutively phosphorylated, negatively regulating ISGF3 binding to DNA; constitutive phosphorylation at T403 maintains STAT2 dimerization with STAT1 [27]. By contrast, IFN-mediated acetylation of STAT2 K390 promotes transcription [28] (Fig.…”
Section: Stat2 Structure and Interactionsmentioning
confidence: 99%